2019
DOI: 10.1021/acs.analchem.9b00176
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Modified Disposable Electrochemical Sensor Strip for Analysis of Fentanyl

Abstract: The increasing prevalence of fentanyl and its analogues as contaminating materials in illicit drug products presents a major hazard to first responder and law enforcement communities. Electrochemical techniques have the potential to provide critical information to these personnel via rapid, facile field detection of these materials. Here we demonstrate the use of cyclic square wave voltammetry (CSWV) with screen-printed carbon electrodes (SPCE), modified with the room temperature ionic liquid (RTIL) 1-butyl-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 38 publications
5
43
0
1
Order By: Relevance
“…Water pollution, [ 1,2 ] environmental toxins, [ 3,4 ] hazardous substances, [ 5,6 ] the rise of synthetic recreational drug alternatives like fentanyl, [ 7–9 ] chemical warfare agents, [ 10,11 ] tumor‐specific molecular indicators, insulin levels in diabetics, glucose levels in hypoglycemics, there is certainly no shortage of unique molecules and chemicals that necessitate a quick, sensitive, and in situ method of sensing their presence, especially in aqueous and bodily environments. To date, there exists a multiplicity of methods [ 4,6,12–14 ] capable of sensing significant analytes like those aforementioned and more, be it chromatography, mass spectrometry, electrochemistry, absorption spectroscopy, or IR and Raman spectroscopies, for example.…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution, [ 1,2 ] environmental toxins, [ 3,4 ] hazardous substances, [ 5,6 ] the rise of synthetic recreational drug alternatives like fentanyl, [ 7–9 ] chemical warfare agents, [ 10,11 ] tumor‐specific molecular indicators, insulin levels in diabetics, glucose levels in hypoglycemics, there is certainly no shortage of unique molecules and chemicals that necessitate a quick, sensitive, and in situ method of sensing their presence, especially in aqueous and bodily environments. To date, there exists a multiplicity of methods [ 4,6,12–14 ] capable of sensing significant analytes like those aforementioned and more, be it chromatography, mass spectrometry, electrochemistry, absorption spectroscopy, or IR and Raman spectroscopies, for example.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that norfentanyl did not present any oxidation peak while 4-ANPP demonstrated two oxidative peaks with better peak resolution than fentanyl, confirming the location of the tertiary amine oxidation. 33 We propose that peak I, seen in our work, for the oxidation of fentanyl cannot be due to oxidation of the tertiary amine present as the amide group in fentanyl as this process more likely occurs through hydrolysis in acidic conditions compared with the buffer pH of 8.5 used herein. Furthermore, we do not support the mechanism explained through the oxidation of the tertiary amine for peak I followed by the oxidation of the product secondary amine for peak II.…”
Section: Hypothesized Redox Mechanismmentioning
confidence: 65%
“…73 The authors further demonstrate the analyte adsorption to the electrode through the lone pairs on the nitrogen atoms. 73 Consideration of the papers mentioned above detailing possible mechanisms for the oxidation of amines, oxidation of cinnarizine by Hegde et al, 74 and work demonstrating fentanyl oxidation by Goodchild et al, 33 as well as this work, may aid in the elucidation of the oxidation mechanism of fentanyl. It was shown that norfentanyl did not present any oxidation peak while 4-ANPP demonstrated two oxidative peaks with better peak resolution than fentanyl, confirming the location of the tertiary amine oxidation.…”
Section: Hypothesized Redox Mechanismmentioning
confidence: 91%
See 2 more Smart Citations